uji kesukaan modifikasi kue klemben dengan substitusi tepung kelapa - Dini Asropi (Universitas Pendidikan Ganesha, 2023)
By using an organoleptic test that evaluates surface texture, crumb texture, aroma, and taste of klemben cake with coconut flour as a substitute, this study wants to determine whether the general public will accept it. Observations using organoleptic tests with four levels, namely very like, like, dislike, and dislike is the approach used in this study to collect data. Using a quantitative descriptive approach, the data is evaluated. Research findings regarding people's preferences for klemben cakes in terms of surface texture are included in the